Onset of optical-phonon cooling in multilayer graphene revealed by RF noise and black-body radiation thermometries. (2nd April 2015) - Brunel, D; Berthou, S; Parret, R; Vialla, F; Morfin, P; Wilmart, Q; Fève, G; Berroir, J-M; Roussignol, P; Voisin, C; Plaçais, B
Abstract: We report on electron cooling power measurements in few-layer graphene excited by Joule heating by means of a new setup combining electrical and optical probes of the electron and phonon baths temperatures. At low bias, noise thermometry allows us to retrieve the well known acoustic phonon cooling regimes below and above the Bloch-Grüneisen temperature, with additional control over the phonon bath temperature. At high electrical bias, we show the relevance of direct optical investigation of the electronic temperature by means of black-body radiation measurements. In this regime, the onset of new efficient relaxation pathways involving optical modes is observed.